Assessing Intercultural Sensitivity: A Case Study of Indonesian EFL Students - Syathroh, Isry Laila; Satriani, Intan; Santoso, Iman (International Journal of English Literature and Social Sciences (IJELS), 2019)
The aim of this paper is to assess Indonesian students’ intercultural sensitivity after taking 600 hours of Intercultural Communication course. The second year students of English Education Department of IKIP Siliwangi have to join Intercultural Communication course for two credit hours. About 36 students were involved in this research. They filled out an Intercultural Sensitivity questionnaire which investigates five dimensions of intercultural sensitivity competence: 1) interaction engagement, 2) respect for cultural differences, 3) interaction confidence, 4) interaction enjoyment and 5) interaction attentiveness. The result of this research reveals that despite the improvement of students’ intercultural sensitivity after taking the 600 hours of Intercultural Communication course, there is still some room available for improvement in terms of the general level of Indonesian students’ intercultural sensitivity. The improvement of intercultural sensitivity will also influence the improvement of intercultural communicative competence.